Impact of innovation ambidexterity on innovation performance moderated by IT competence of SMEs / Hardi Emrie Rosly, Rohana Ngah and Noor Faizah Lajin - Rosly, Hardi Emrie; Ngah, Rohana; Lajin, Noor Faizah (Faculty of Business and Management, 2023)
This paper aims to explore the impact of innovation ambidexterity on innovation performance moderated by the IT competency of SMEs. In this research, the innovation ambidexterity variable serves as an independent variable, innovation performance serves as a dependent variable, and information technology knowledge and information technology operations support (IT competency) serve as moderating variables. An online survey was used to do a purposeful random sampling, and then the data from that survey were analysed using the structural equation modelling capabilities of SMART PLS. Innovation ambidexterity and innovation performance are positively correlated, but this research was unable to pinpoint the function that IT competency played in moderating this link. This finding is quite intriguing because it deviates significantly from earlier research, which primarily demonstrated that IT competencies acted in a complementary or co-specialized function to other resources. This research contributes to the literature on the antecedents of innovation performance. SMEs that want to enhance their innovation performance may find the research helpful in optimising the use of their limited resources to remain competitive in the current business landscape.